Exploring the Effects of the Home and Classroom Literacy Environments on Emergent Literacy: A Multilevel Model Analysis - Bready, Mary (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Child Development.; Advisor: Calvin Gidney.; Committee: Sara Johnson, and Catherine Snow.; Keywords: Education, and Reading instruction.